The effect of social support on academic resilience among Indonesian university students: The mediating role of emotion regulation strategies - Edilburga Wulan Saptandari; Sekar Larasati Suryandari; Marsyanti Mahira (Universitas Mercu Buana Yogyakarta, 2025)
University students often face challenges to their resilience due to factors like academic pressure. These stressors can lead to mental health issues like anxiety and depression, highlighting the need for resilience-building strategies. Previous studies in Indonesia and worldwide have demonstrated that social support and emotion-regulation strategies significantly influence academic resilience among university students. However, no study has explored the mediating role within the interrelationships among these variables, particularly the mediating role of multi-aspect emotion regulation constructs, namely cognitive reappraisal and expressive suppression. This study aims to evaluate the mediating roles of these two aspects of emotion regulation in the relationship between social support and academic resilience among Indonesian university students. The respondents consisted of 219 students aged between 17 and 33 years (M = 21.219, SD = 2.013). These respondents were recruited using a nonprobability sampling technique. They completed instruments measuring social support, emotion regulation, and academic resilience. The correlational analysis provided initial evidence supporting the relationships among social support, emotion regulation, and academic resilience. Path analysis showed that mediation analysis revealed cognitive reappraisal significantly explained the variance in the relationship between social support and academic resilience through partial mediation. In contrast, expressive suppression did not show a significant mediating role. Overall, the results suggest a relationship between social support and academic resilience, indicating that positive social support enhances cognitive reappraisal and thereby increases students' academic resilience. The implications of this study suggest that social support and emotional regulation are crucial factors in improving the academic resilience of Indonesian students, and these findings can serve as a valuable reference for educators and policymakers. Keywords: Academic resilience, emotion regulation, mediation, social support, university students